Extensive neurological recovery from a complete spinal cord injury: a case report and hypothesis on the role of cortical plasticity - Choe, Ann S.; Belegu, Visar; Yoshida, Shoko; Joel, Suresh; Sadowsky, Cristina L.; Smith, Seth A.; van Zijl, Peter C.; Pekar, James J.; Mcdonald, John W. (Frontiers in Human Neuroscience, 2013)
Neurological recovery in patients with severe spinal cord injury (SCI) is extremely rare. We have identified a patient with chronic cervical traumatic SCI, who suffered a complete loss of motor and sensory function below the injury for six weeks after the injury, but experienced a progressive neurological recovery that continued for 17 years. The extent of the patient’s recovery from the severe trauma-induced paralysis is rare and remarkable. A detailed study of this patient using diffusion tensor imaging (DTI), magnetization transfer imaging (MTI), and resting state fMRI (rs-fMRI) revealed structural and functional changes in the central nervous system that may be associated with the neurological recovery. 62% cervical cord white matter atrophy was observed. DTI-derived quantities, more sensitive to axons, demonstrated focal changes, while MTI-derived quantity, more sensitive to myelin, showed a diffuse change. No significant cortical structural changes were observed, while rs-fMRI revealed increased brain functional connectivity between sensorimotor and visual networks. The study provides comprehensive description of the structural and functional changes in the patient using advanced MR imaging technique. This multimodal MR imaging study also shows the potential of rs-fMRI to measure the extent of cortical plasticity.